Chenjiagou: The History of the Taiji Village - Gaffney, David (Revista de Artes Marciales Asiáticas, 2012)
This article explores how various political, social, and environmental factors helped to shape the face of taijiquan in the art's birthplace, Chenjiagou. By looking at the impact of the some of the major historical Chen taijiquan figures and examining the social context within which they operated, we can better understand the system's evolution. Research included a number of visits to Chenjiagou, where the author interviewed some of the leading Chen Style teachers, as well as an examination of published literature in the fields of both taijiquan and wider political and economic commentaries. Literature included both historical records and up-to-date studies. In spite of outside intrusion, great social and economic hardship, and inevitably changing lifestyles, Chenjiagou has managed to hold onto its martial traditions and looks set for a bright future in the twenty-first century.